Protective effect of dexmedetomidine against delayed bone healing caused by morphine via PI3K/Akt mediated Nrf2 antioxidant defense system - Lou, Yani; Zou, Linfang; Shen, Zhenyu; Zheng, Jianwei; Lin, Yuanqu; Zhang, Zhe; Chen, XuanKuai; Pan, Jun; Zhang, Xutong (Frontiers in Pharmacology, 2024)
Background: As a class of analgesics, opioids are frequently used to treat both acute and chronic moderate to severe pain.Patients frequently receive opioid painkillers after orthopedic accidents or surgeries. Evidence suggests that opioid drug users have a 55.1% higher risk of fracture and poor bone repair than non-users of opioid drugs.The key pathogenic alterations in the incidence and progression of poor bone repair are over apoptosis and aging of osteoblasts due to the stress caused by oxidation. Dexmedetomidine (Dex) has been proven to protect against a variety of degenerative illnesses by reducing oxidative stress. However, nothing is known about how it affects bone repair.Methods: PI3K/Akt/Nrf2 pathway was detected by immunofluorescence and western blot. SOD, CAT, JC-1, DHE and mitosox were used in the Oxidative Stress.Micro-CT,H&E and Masson's staining,immunohistochemically were performed to evaluate the therapeutic effects of DEX on calvarial defects in the morphine-induced rat model.Results:We found that morphine-induced an imbalance in the metabolism and catabolism of primary rat Osteoblasts. However, these conditions could be inhibited by DEX treatment. In the meantime, DEX induced the expression of Nrf2-regulated antioxidant enzymes such as NQO1, HO-1, GCLm, GCLc, and TrxR1. DEX-mediated Nrf2 activation is linked to the PI3K/Akt signaling system.Furthermore, it has been established that intravenous DEX enhanced the growth of bone healing in a model of a surgically produced rat cranial lesion.Conclusions: This is the first description of the unique DEX mechanism acting as a Nrf2 activator against morphine-mediated oxidative harm, raising the possibility that the substance may be used to prevent bone defects.